2022
DOI: 10.1111/iwj.13765
|View full text |Cite
|
Sign up to set email alerts
|

The association between estimated glomerular filtration rate and prognosis in patients with diabetic foot osteomyelitis

Abstract: We aimed to explore the association between estimated glomerular filtration rate (eGFR) and prognosis in patients with diabetic foot osteomyelitis (DFO).Three hundred twenty-one DFO inpatients were enrolled and classified into four groups according to the eGFRs as follows: normal (≥90), mildly reduced (60-89), moderately reduced (30-59) and severely reduced (<30). These patients were followed-up for 6 months to observe the outcomes, including ulcer healing and amputation. The associations between eGFR and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…A multicenter study revealed that the diabetic patient with even moderate CKD(eGFR<60ml/min per 1.73m 2 ) had an increased risk for DFU and LEA (51). The eGFR<30ml/min per 1.73m 2 in DFU patients with osteomyelitis was an independent predictor for amputation and healing failure (52). However, in this study, we found the mean eGFR value in the amputated patients was over 60 mL/min per 1.73 m 2 , which was higher than that in the nonamputees.…”
Section: Discussioncontrasting
confidence: 76%
“…A multicenter study revealed that the diabetic patient with even moderate CKD(eGFR<60ml/min per 1.73m 2 ) had an increased risk for DFU and LEA (51). The eGFR<30ml/min per 1.73m 2 in DFU patients with osteomyelitis was an independent predictor for amputation and healing failure (52). However, in this study, we found the mean eGFR value in the amputated patients was over 60 mL/min per 1.73 m 2 , which was higher than that in the nonamputees.…”
Section: Discussioncontrasting
confidence: 76%
“…The fumigation and washing method of traditional Chinese medicine are not difficult to operate and have little side effects, so it is worth recommending. 36 patients with grade 0 DF were treated with self-made Huoxue Tongluo foot bath prescription (Wuzao snake, safflower, Chuanxiong, Achyranthes bidentata, Angelica sinensis, chicken blood vine, and clinical addition and subtraction) by Xu Hongtao [ 35 ]. After 8 weeks of treatment, the total effective rate reached 86.…”
Section: Traditional Chinese Medicine Treatment Of Dfmentioning
confidence: 99%
“…Statistically, patients with PAD or RI had poorer long‐term survival, with more than half of the deaths due to cardiovascular events 44 . RI patients can suffer from peripheral tissue oedema due to an increased rate of urinary albumin excretion, further exacerbating tissue oxidation and inflammatory responses 46 . Also, renal anaemia reduces the oxygen supply to the tissues and hypertension due to kidney diseases can cause endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%